Integrated computer forensic investigation model based on Malaysian standards - Perumal, S; Norwawi, NM (Inderscience Enterprises Ltd, 2024)
With the proliferation of the digital crime around the world, numerous digital forensic investigation models are already being developed. In fact, many of the digital forensic investigation models focus on technical implementation of the investigation process as most of it were developed by traditional forensic expert and technologist. As an outcome of this problem, most of the digital forensic practitioners focus on technical aspect and forget the core concept of digital forensic investigation model. In this paper, we are introducing a new digital forensic investigation model which will capture a full scope of an investigation process based on Malaysian cyber law. The proposed model is also compared with the existing model which is currently available and being applied in the investigation process.